Design and Development of Can Crushing Machine - Chakule, Rahul; Patil, Supriya; Talmale, Poonam (Asian Journal of Engineering and Applied Technology, 2020)
A can crusher machine is used to crush the cans for storing in bin efficiently. The crushing of cans plays a significant role in economy and ultimately helps to society. The process of cans crushing is also human and environment friendly. From literature studies it was learnt that the existing cans crushing machines are automated and can overcome the limitation of manually crushing but cost of automated cans crushing machine is high. In present study, the can crusher machine is developed economically which is automatic and eco-environment friendly. The experiments were conducted for finding the optimal pressure and force values required for effectively crushing the cans. This work helps to increase the storing capacity of cans for user. Thus, transportation cost reduces significantly due to process improvement efficiency.